Indonesia’s Strategy in Facing the Regional Comprehensive Economic Partnership (RCEP) - Dwi F. Moenardy; SintiaCatur Sutantri; Djoko Roespinoedji; MohdHaizam Saudi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article intends to explain how Indonesia's strategy is to face the Regional Comprehensive Economic Partnership (RCEP). RCEP, which was inaugurated in November 2012, is an ASEAN initiative in promoting trade relations between ASEAN member countries (Indonesia, Brunei Darussalam, Philippines, Cambodia, Malaysia, Laos, Myanmar, Singapore, Thailand, and Vietnam) with its main trading partners in the Asia Pacific region, namely China, India, Australia, Japan, South Korea, and New Zealand. RCEP has the potential to provide significant opportunities for business in the East Asia region because RCEP member countries represent nearly half of the world's population and contribute around 30 percent of global Gross Domestic Product and more than a quarter of world exports. This research is qualitative by collecting data through library research. The analysis knife in this research is adding an article on international trade and international cooperation. The results of this study conclude that RCEP has had a negative and positive impact on Indonesia. Collaboration between the government and exporters from Indonesia, regulations for multinational companies from other countries that set up factories or companies in Indonesia to use Indonesian workers, establish cooperative relationships with countries that are trading opponents of China, improve the quality of labor, regional politics and SMEs so that Indonesia is not only a target market, and protection of farmers related to the monopoly of seeds and medicines are forms of internal and external strategies that can be applied in the face of the Regional Comprehensive Economic Partnership (RCEP).